PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS PELANGGAN PADA PRODUK LE MINERALE UKURAN 600ML (Studi Pada Mahasiswa Politeknik Negeri Malang) - Gita Andini; Asminah Rachmi; Baroroh Lestari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The increasingly intense competition in bottled drinking water (AMDK) industies encourages companies to attract customers and maintain customers' loyalty. This study aims to identify and analyze the influence of brand image and brand trust on customers' loyalty toward Le Minerale 600ml products among students of Politeknik Negeri Malang. This study used a quantitative method with a purposive sampling technique. The sample consisted of 142 active students of Politeknik Negeri Malang who had purchased Le Minerale 600ml at least three times during the first three months of 2025. The data were then collected through questionnaires and analyzed using multiple linear regression and hypothesis testing. The results of the study show that brand image and brand trust both partially and simultaneously have a positive and significant effect on customer’s loyalty. Based on these findings, it can be concluded that the company needs to maintain and improve its brand image and continuously build customer trust in order to sustain customers' loyalty toward Le Minerale products. This finding can be utilized by companies to enhance customer’s loyalty through strengthening brand image.